The economic consequences of extending the use of fair value accounting in regulatory capital calculations - Chircop, Justin; Novotny-Farkas, Zoltán (Journal of Accounting and Economics, 2016)
We investigate the economic consequences of the Basel III requirement to include unrealized fair value gains and losses on available-for-sale (AFS) securities in regulatory capital. Using data for U.S. banks we find negative market reactions around news indicating an increased likelihood of this regulatory change being implemented, consistent with increased regulatory costs. We also find that banks affected by this regulation reduce their investment in risky AFS securities relative to unaffected banks. This result suggests that extending the use of fair values for regulatory purposes reduces ex ante risk taking.